Wild at heart : discovering the secret of a man's soul - Eldredge, John, 1960- (Nashville, Tenn. : T. Nelson, 2001)
Eldredge believes that rather than being a Really Nice Guy, every man, "longs for battles to fight, an adventure to live, and a beauty to rescue."
Includes bibliographical references.
Keywords: Christian men -- Religious life; Masculinity -- Religious aspects -- Christianity